2018
DOI: 10.1021/acs.energyfuels.8b02886
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy for Fuel Desulfurization by Molecular Inclusion with Copper(II)-β-cyclodextrin@SiO2@Fe3O4 for Removing Thiophenic Sulfides

Abstract: Developing a new and environment-friendly desulfurization strategy for removing thiophenic sulfides from fuel is currently necessary. Fuel desulfurization by molecular inclusion with a novel cyclodextrin-based magnetic nanomaterial copper(II)-β-cyclodextrin@silica@ferroferric oxide (Cu(II)-β-CD@SiO 2 @Fe 3 O 4 ) was proposed for the efficient removal of thiophene (T), benzothiophene (BT), and dibenzothiophene (DBT) in fuel. Cu(II)-β-CD@SiO 2 @Fe 3 O 4 was successfully prepared by the reaction between mono-6-O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For example, Moradi et al recently stabilized Cu(II)/β-CD complexes over fibrous nanosilica and successfully employed the material as a catalyst in the synthesis of oxazolidinones [41]. Xia and co-workers prepared a magnetically-recoverable catalyst made of Cu(II)/β-CD complexes anchored over ferric oxide and covered by silica [42]. Shafiee et al reported the preparation of functionalized PEGylated mesoporous silica nanoparticle-graphene oxide as a catalyst for the synthesis of imidazoles [43].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Moradi et al recently stabilized Cu(II)/β-CD complexes over fibrous nanosilica and successfully employed the material as a catalyst in the synthesis of oxazolidinones [41]. Xia and co-workers prepared a magnetically-recoverable catalyst made of Cu(II)/β-CD complexes anchored over ferric oxide and covered by silica [42]. Shafiee et al reported the preparation of functionalized PEGylated mesoporous silica nanoparticle-graphene oxide as a catalyst for the synthesis of imidazoles [43].…”
Section: Introductionmentioning
confidence: 99%
“…However, a fluorine (F) atom existing in the CDP would cause harm to the environment, and the separation performance of the CD polymers was not satisfactory in the desulfurization process. Then a cyclodextrin-based magnetic desulfurization agent (Cu(II)−βCD@SiO 2 @Fe 3 O 4 ) 40 was developed to improve the environmental friendliness and separation performance of the CD polymers. However, the synthesis process was cumbersome, and a large amount of organic solvent was used.…”
Section: Introductionmentioning
confidence: 99%